2021
DOI: 10.1038/s41598-021-82158-8
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-first century droughts have not increasingly exacerbated fire season severity in the Brazilian Amazon

Abstract: Biomass burning in the Brazilian Amazon is modulated by climate factors, such as droughts, and by human factors, such as deforestation, and land management activities. The increase in forest fires during drought years has led to the hypothesis that fire activity decoupled from deforestation during the twenty-first century. However, assessment of the hypothesis relied on an incorrect active fire dataset, which led to an underestimation of the decreasing trend in fire activity and to an inflated rank for year 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 84 publications
(91 reference statements)
2
44
0
6
Order By: Relevance
“…Since 2012, rates of deforestation across the BLA have increased by a factor of two, with 10 129 km 2 deforested in 2019 (Barlow et al, 2019;Assis et al, 2019). The impact of this increased deforestation on the amount of fire is still uncertain (Libonati et al, 2021;van Marle et al, 2017;Aragão et al, 2018) and the impacts on air quality have not yet been fully assessed. To estimate the impact of increased deforestation on fire, we developed a model to predict dry season active fire count based on climate and deforestation.…”
Section: Accepted Articlementioning
confidence: 99%
“…Since 2012, rates of deforestation across the BLA have increased by a factor of two, with 10 129 km 2 deforested in 2019 (Barlow et al, 2019;Assis et al, 2019). The impact of this increased deforestation on the amount of fire is still uncertain (Libonati et al, 2021;van Marle et al, 2017;Aragão et al, 2018) and the impacts on air quality have not yet been fully assessed. To estimate the impact of increased deforestation on fire, we developed a model to predict dry season active fire count based on climate and deforestation.…”
Section: Accepted Articlementioning
confidence: 99%
“…Jiménez-Muñoz et al [49] found that up to 13% of Amazonian tropical forests endured extreme drought at the beginning of 2016, which set the conditions for more extreme forest fires in 2017. On the other hand, the year 2013 was classified as exceptionally wet based on the positive rainfall anomalies and a short dry season [11]. These conditions did not promote high intensity forest fires and therefore, we observed the lowest number of extreme fires (179 events, Fig.…”
Section: Temporal Variabilitymentioning
confidence: 67%
“…The establishment and enforcement of the Action Plan to Prevent and Control Deforestation in the Brazilian Legal Amazon (PPCDAm) in 2004, together with the Soy Moratorium in 2006, and the Zero-Deforestation Cattle Agreements in 2009 allowed to progressively reduce deforestation rates from 2005 onwards [9,10]. While the use of fire in deforestation was an accepted paradigm for a long time, Aragão et al [11] suggested a decoupling a e-mail: canocrespoana@gmail.com (corresponding author) between deforestation and fire because the decrease in fire activity was not as strong as the decline in deforestation during the period 2003-2015. However, Libonati et al [12] revisited the decoupling hypothesis recently and found a much weaker decoupling for the same period, which consequently reinforces the role of deforestation as a major driver of fire in Amazonia.…”
Section: Introductionmentioning
confidence: 99%
“…Among these dysfunctions, we highlight the transformations in its landscape promoted by government policies to encourage the occupation of the region, the expansion of agricultural activity and the construction of major infrastructure works such as highways and hydroelectric dams; actions that have historically promoted deforestation in the Amazon (Cochrane, 2003;Becker, 2005;Fearnside, 2006;Ferrante and Fearnside, 2020;Libonati et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Given the gap in knowledge about the inflection point of the forest, as a precautionary measure strong efforts should be made to conserve the Amazon Forest yet standing (Fearnside, 2009;Nobre and Borma, 2009). However, the number of fires in the Amazon has intensified in recent years, driven by the increase in deforestation (Silveira et al, 2020;Libonati et al, 2021). About 1/3 of the fire occurrences between 2003 and 2019 occurred up to 1 km away from deforested areas in the same year and up to 500 m from deforested areas in the previous year; in 2019, fires occurred Rev.…”
Section: Introductionmentioning
confidence: 99%